2023
DOI: 10.3390/ijerph20032009
|View full text |Cite
|
Sign up to set email alerts
|

Urban Itineraries with Smartphones to Promote an Improvement in Environmental Awareness among Secondary School Students

Abstract: Our world is undergoing a series of changes that are taking it to an unsustainable situation. In addition to alerting the population, we must seek education towards a more sustainable world. This research proposes the realization in Alcoy (Spain) of some urban itineraries with mobile devices and with secondary school students, in order to promote an improvement in awareness and action on environmental problems. This activity aims, among other objectives, through informal learning and outside the classroom, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Activities utilizing the PlantNet mobile application provide more permanent information about plant species than computer‐based digital herbarium activities (Iskrenovic‐Momcilovic, 2020 ). As a result of plant identification activities conducted with PlantNet, it was observed that students' plant identification skills improved significantly (Santri et al., 2021 ), and a significant improvement was observed in students' awareness and levels of concern about environmental problems (Álvarez‐Herrero, 2023 ). Secondary school students used PlantNet, traditional image‐based printed identification keys, and unstructured searches on the Internet to identify plants and stated that PlantNet was the least difficult of these methods (Lang & Šorgo, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Activities utilizing the PlantNet mobile application provide more permanent information about plant species than computer‐based digital herbarium activities (Iskrenovic‐Momcilovic, 2020 ). As a result of plant identification activities conducted with PlantNet, it was observed that students' plant identification skills improved significantly (Santri et al., 2021 ), and a significant improvement was observed in students' awareness and levels of concern about environmental problems (Álvarez‐Herrero, 2023 ). Secondary school students used PlantNet, traditional image‐based printed identification keys, and unstructured searches on the Internet to identify plants and stated that PlantNet was the least difficult of these methods (Lang & Šorgo, 2022 ).…”
Section: Introductionmentioning
confidence: 99%